Mutations in TP53 and CTNNB1 in Relation to Hepatitis B and C Infections in Hepatocellular Carcinomas from Thailand (2011)
ABSTRACT: Hepatocellular carcinoma (HCC) may develop according to two major pathways, one involving HBV infection and TP53 mutation and the other characterized by HCV infection and CTNNB1 mutation. We have investigated HBV/HCV infections and TP53/CTNNB1 mutations in 26 HCC patients from Thailand. HBV DNA (genotype B or C) was detected in 19 (73%) of the cases, including 5 occult infections and 3 coinfections with HCV. TP53 and CTNNB1 mutations were not mutually exclusive, and most of TP53 mutations were R249S, suggesting a significant impact of aflatoxin-induced mutagenesis in HCC development.